2013
DOI: 10.1007/s11096-013-9844-2
|View full text |Cite
|
Sign up to set email alerts
|

Initiatives promoting seamless care in medication management: an international review of the grey literature

Abstract: Although not all initiatives are applicable as such to a particular healthcare setting, most of them convey very interesting data that should be used when drawing recommendations and implementing approaches to optimize continuity of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…An international review of regional and national initiatives relating to medicines at care transitions identified the importance of local implementation strategies in ensuring regional and national initiatives and policies work effectively. 6 This study has provided insights into how local policies can be refined.…”
Section: Resultsmentioning
confidence: 99%
“…An international review of regional and national initiatives relating to medicines at care transitions identified the importance of local implementation strategies in ensuring regional and national initiatives and policies work effectively. 6 This study has provided insights into how local policies can be refined.…”
Section: Resultsmentioning
confidence: 99%
“…The roles pharmacists can play in improving patient safety at care transitions are well documented [ 22 , 23 ]. Activities mainly encompass medication reconciliation [ 24 26 ], patient education programmes and post-discharge follow-up [ 22 , 23 , 27 29 ] and medication reviews [ 22 , 23 , 27 ]. By demonstrating that pharmacists can safely write discharge medication orders, the present study has expanded the evidence-base regarding pharmacist-led discharge activities.…”
Section: Discussionmentioning
confidence: 99%
“… 66 Ongoing efforts to reach truly seamless care will be strengthened with leadership, tailoring strategies to the local setting and information technology support. 19 …”
Section: Communicationmentioning
confidence: 99%
“…This has been driven mostly from the identification of these events as having an increased risk for information transfer to be suboptimal, which can lead to errors and omissions regarding medication therapy. 19 21 This can result in an increased risk of an ADE, which includes adverse drug reactions (ADRs) or another type of drug-related problem (DRP). Unfortunately, the evidence also shows that many of these ADEs are potentially preventable.…”
Section: Introductionmentioning
confidence: 99%